Implementation of STEM education in the process of training of future specialists of engineering and pedagogical specialties - Derevyanchuk, o.v.; Kovalchuk, V.I.; Kramar, V.M. (SPIE, 2024)
The article reveals the role of STEM education in today’s technological society and its impact on the development of students’ skills, necessary for building career in the modern world. The need to modernize methodological principles, educational content, and educational technologies is emphasized. Initial, basic, profile, higher/professional levels of STEM education development are described. The directions of STEM education in training of future specialists of engineering and pedagogical professions are highlighted. The STEM project “Spectroscope” was implemented to test innovative method of studying the phenomenon of light dispersion by means of robotics.
For the students that interests to STEM disciplines and involving them in career building in the related fields, which is ensured by implementing the integration of disciplines.
Keywords: Education and training, Robotics, Computer programming, Engineering, Light sources,